The Language of Violence: Aggression as a Narrative and Thematic Device in Literature - Neupane, Dasarath; Lourdusamy, Arputhem (NPRC Journal of Multidisciplinary Research, 2025)
This paper, therefore, investigates the representation of aggression in English literature, taking into consideration thematic and narrative meaning in various periods and genres. This research uses selected literary works qualitatively to show how the manifestations of aggression through physical, psychological, and systemic violence have constituted a prism on which power, identity, gender dynamics, and social inequality have been discussed. The research shows how aggression develops the character, the plot, and reader involvement, even while it also raises moral and ethical questions. By locating aggression within both historical and cultural contexts, the research underlines its enduring relevance as a motif that reflects values and complexities of life. Results broaden the general view on aggression in literature by offering an insight into its manifold faces and impacts readers may get from it. This work thus encourages further investigations on the intersection of aggression with other themes and representations across a number of traditions.